1,1′-Dibromoferrocene - Hnetinka, Chrissy A.; Hunter, Allen D.; Zeller, Matthias; Lesley, M. J. Gerald (Acta Crystallographica Section E-structure Reports Online, 2004)
The structural properties of 1,1′-dibromoferrocene, [Fe(C 5H4Br)2, were investigated using single-crystal x-ray diffraction. It was found to crystallize in the non-centrosymmetric space group P21. Despite of the steric demand of the two bromine substituents, the two cyclopentaldienyl (Cp) rings were found to exhibit an eclipsed conformation in the solid state. The conformational arrangement found in compound seems not to be the result of general electronic preference within this class of compounds, but has to be attributed to crystal packing effects in the solid state.
11 citations (Crossref) [2023-10-31] Citation Key Alias: pop00202 tex.type: [object Object]
Keywords: Bromine compounds; Conformations; Crystal packing; Crystal structure; Crystallization; Derivatives; Ligands; Molecular structure; Organometallics; Pseudo-torsion angle; Single crystals; Solid state structures; Synthesis (chemical); X ray diffraction; dept.che

p‐Anisolecarbonitrile - Lesley, M. J. Gerald; Pineau, Mark R.; Hunter, Allen D.; Zeller, Matthias (Acta Crystallographica Section E: Crystallographic Communications, 2004)
The structure of p-anisolecarbonitrile, C8H7NO, was determined by single-crystal X-ray diffraction at 100 K. It crystallizes in the monoclinic space group P21/c with two crystallographically independent molecules in the asymmetric © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00236 tex.type: [object Object]
Keywords: Aromatic rings; Asymmetric units; Bond length; Chemical bonds; Complexation; Crystal atomic structure; Crystal symmetry; Crystallography; Derivatives; Nitrogen compounds; Parallel stacks; Synthesis (chemical); X ray diffraction; dept.che